Development of Virtual Geography Laboratory to Improve Cognitive Learning Outcomes and Spatial Capabilities Social Sciences Education - Prasetya, Sukma Perdana; Prasetyo, Ketut; Budiyanto, Eko; Rindawati, Rindawati; Murtini, Sri; Fadirubun, Fahmi Fahrudin; Dock, Chanthoeurn (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2024)
This project aims to develop a website that functions as a virtual laboratory for studying geography topics that is suitable for use, as well as testing its effectiveness on cognitive learning outcomes and spatial abilities. The research uses the Borg and Gall development model, which is then summarized and divided into three main activities: introduction, development, and testing. Subject selection was based on the cluster random sampling technique. The subjects consisted of Class Learning outcome data was collected using questionnaires, interviews, pretests and posttest, analyzed using descriptive statistical tests and Mancova inferential statistics. Research Results: 1) the development of a geographic virtual laboratory is suitable for use according to material experts and received the